A critical analysis of South African underground comics - Breytenbach, Jesse-Ann (Rhodes University, Faculty of Humanities, Department of Fine Art, 1996)
In a critical analysis of several independantly produced South African comics of the 1980s and early 1990s, close analysis of the comics leads to an assessment of the artists'intentions and purposes. Discussion of the artists' sources focuses on definitions of different types of comics. What is defined as a comic is usually what has been produced under that definition, and these comics are positioned somewhere between the popular and fine art contexts. As the artists are amateurs, the mechanical structure of comics is exposed through their skill in manipulating, and their initial ignorance of, many comic conventions. By comparison to one another, and to the standard format of commercial comics, some explanation of how a comic works can be reached. The element of closure, bridging the gaps between frames, is unique to comics, and is the most important consideration. Comic artists work with the intangible, creating from static elements an illusion of motion. If the artist deals primarily with what is on the page rather than what is not, the comic remains static. Questions of quality are reliant on the skill with which closure is implemented. The art students who produced these comics are of a generation for whom popular culture is the dominant culture, and they create for an audience of peers. Their cultural milieu is more visual than verbal, and often more media oriented than that of their teachers. They must integrate a fine art training and understanding into the preset rules of a commercial medium. Confronted with the problem of a separation of languages, they evolve a new dialect. Through comparative and critical analyses I will show how this dialect differs from the language of conventional comics, attempting in particular to explain how the mechanics of the cornie medium can limit or expand its communicative potential.
Keywords: Underground comic books, strips, etc. -- South Africa -- History and criticism